Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 995808662 species occurrences available in GBIF matching the query: { "and" : [ "Year 1600-2020", "HasCoordinate is true", "TaxonKey is Animalia", "HasGeospatialIssue is false" ] } The dataset includes 995808662 records from 15119 constituent datasets: 35 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 19 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 1285 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 85 records from Neogene palynomorpha from site 81-552. 120 records from BIRDRACE The early birds. 1405 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 1289 records from RECORD Orthoptera Data. 8 records from Analyses of the recent components of sediment core PS1277-1. 47 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 15 records from Inventaire des mammifères du Parc de la Haute-Île (93). 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 30 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 10 records from Oberservation of birds at station PS14/143 along 49° West. 11 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 10 records from Données bibliographiques ASFRA. 31 records from Naturschutzgebiet Müchelholz (Mücheln). 22 records from Microzooplankton abundance and biomass at station TT043_27-1. 31 records from Wiese am Waldrand (Gurtweil). 5 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 11 records from Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae). 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 147049 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 43 records from Renaturierung Werse (Innenbereich Beckum). 380 records from UWYMV Herpetology Collection (Arctos). 23 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 248 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 245 records from Atlantic Forestry Centre Insect Reference Collection. 4476 records from Midden-Limburg Fish Ponds Survey. 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 11452 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 4 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 1 records from marine sediment metagenome Raw sequence reads. 9 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 20191 records from Seabirds in Norway - Estimated population sizes. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 11 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 4 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 16 records from Kenai National Wildlife Refuge, Alaska (KNWR) Fish observations (Arctos). 2 records from Geometridae de France métropolitaine. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 1 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 442 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 17 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 1 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 4185 records from Leicestershire and Rutland Aculeate Records. 2 records from Two new species of Spider Wasps (Hymenoptera, Pompilidae), Ctenagenia pagliano from Lebanon and Evagetes liane from Canary Islands. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 113 records from South Lanarkshire peatland records 2013. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 8 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 16539 records from Suivi Temporel des Libellules (STELI). 75 records from Données du/de la naturaliste GAUTHIER Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 1649 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 723 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 100 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 205279 records from First Bird Atlas. 15151 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 661 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 1 records from Reptilia ZMK. 70 records from Ensemble des données Orthoptères. 4170 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 6 records from Pauximyia, a new genus of Odiniidae (Diptera: Acalyptratae) with description of two new species from Brazil. 280 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 31 records from Lepidurus arcticus survey Northeast Greenland 2013. 187 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 90 records from Natura 2000 Vallée de la Seille. 10045 records from Inventario de Hymenóptera; parasítica en México. 48 records from VSN-Wiese. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 791 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 4792 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 190 records from Relative abundance of ostracods in sediment core Sv09. 910 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 165 records from Ecological study of the plankton in the port of Ostend in 1965. 709 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 5 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 93324 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 49 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 9 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 1533 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 76 records from BIRDRACE Nachtigallen. 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 6 records from Données naturalistes de THÉVENOT Jessica. 119 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1850 records from Trondheim urban biodyversity survey. 3 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 81 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 186 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 11 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 454 records from Lucanidae. 660 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 27268 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 70 records from Birds Specimens of Akita Prefectural Museum. 217 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 8694 records from UAM Fish Collection (Arctos). 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 8808 records from Survey of bumblebees in central Alberta - 2018. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 2 records from New data on the taxonomy and distribution of Philippine Ochodaeidae and description of a new species from Central Visayas (Coleoptera: Scarabaeoidea). 78 records from Isotope tracer experiment: meiofauna counts. 19 records from Données naturalistes de LE GLOANEC Vincent. 117837 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-71, 1974-5. 32 records from MSUM Ichthyology and Herpetology Collections. 25 records from Bird Specimens of The Cattle Museum. 557 records from Corn bunting breeding distribution in Scotland. 7122 records from Whale catches in the Southern Ocean. 14 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 22 records from Benthic macrofauna abundance of sediment core 13200-008. 900 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 71 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 2082 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 2510 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 3 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 269 records from South American Antarctic Marine Biodiversity Literature. 6 records from Arizona State University Vascular Plant Herbarium. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 35 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 43 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 3 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 2 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 29 records from Données espèces - Expertise IPE 70. 22 records from Ostracoda abundance of Hole 24-238. 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 575 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 15 records from Meiofauna abundance in sediment core 54301-010. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 111 records from Collection Hydrozoa - ZSM München. 3561 records from Biogeography of near-shore reef fishes in northern New Zealand. 2815 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 17 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 90 records from Steinbruch Mainz-Weisenau, 2. Jahr. 9053 records from NE Scotland other invertebrate records 1800-2010. 2172 records from ConDidact Citizen Science Surveys - Snails 2006. 20 records from Description of lithologic section units of IODP Hole 325-M0033A. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. GEPOG & LPO. 16 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 36 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 43 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 97 records from Données opportunistes odonates récoltées par le CPIE Seignanx et Adour entre 2011 et 2015. 125 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 30 records from Schulgelände (Wetter). 89 records from Deponie Klausdorf. 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 14973 records from Données Entomologiques A. HORELLOU 1988-2018. 16 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 2 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 2387 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 13212 records from Enquête Lucane. 6 records from Dinoflagellate abundance of Hole 81-555. 432 records from Erlengraben/Lipp-Tal (Östringen). 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1985 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 1 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 2 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 378 records from Expédition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 1484 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 3 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 314 records from EDIT - ATBI in Gemer area (Slovakia). 1 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 21772 records from Global compendium of Aedes albopictus occurrence. 325 records from Inventaire malacologique de la RNR des Marais de Stors. 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 2508 records from BioGIS - Reptiles - HUJ collections. 40 records from Teich Berlin Wuhlheide. 1 records from Analyses of the recent components of sediment core PS1222-1. 48 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 17 records from AKG-Gelände (Bensheim). 1 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 4156 records from Fishes in the Argentine Sea from 1967 to the present time. 3973 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 79 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 84 records from Ostracoda abundance of Hole 48-403. 134 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 560260 records from Queensland Museum provider for OZCAM. 5 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 2073 records from Données naturalistes de Monsieur LAFAGE Denis. 5 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 75 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 9115 records from Données d'observations d'orthoptères en Auvergne, d'Emmanuel Boitier, de 1998 à 2015.. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 1 records from Range table from benthic foraminifers in ODP Hole 146-889B. 26 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 701 records from Données naturalistes d'Arnaud LE NEVÉ. 23675 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 9 records from Analyses of the recent components of sediment core PS1219-1. 717 records from Redland City Council Citizen Science Portal. 180 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 4 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 1 records from New Zealand forest-dwelling skinks of the Oligosoma oliveri (McCann) species-complex (Reptilia: Scincidae): reinstatement of O. pachysomaticum (Robb) and an assessment of historical distribution ranges. 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 78 records from Steinbruch Mainz-Weisenau, 3. Jahr. 949 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 512 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 11 records from Pollen profile V and Ausfluss at Krumbach, Germany. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 175774 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 5 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 355 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 1 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 34 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 718 records from Bird species occurrences recorded from selected sites in mid Tana River Basin, Kenya. 365 records from Données du naturaliste PROVOST romain provenant de la base de donnée du SINP Île-de-France CETTIA. 66 records from Wildlife Sightings in the City of Logan. 16133 records from Birds Specimens. 55 records from Schulgelände Kranich-Gymnasium (Salzgitter). 92 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 33 records from Fliegenhaupt Marksuhl. 66 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 17766 records from DMNS Mammal Collection (Arctos). 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 881 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b). 78 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 1 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 60 records from Artenvielfalt auf dem Schulgelände. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 1 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 43 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 5 records from New data on jumping spiders of Iran, with a new species of Salticus (Araneae: Salticidae). 117 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 1319 records from National Museum of Natural Science. 1870 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 165 records from Diversidad de anfibios en tres coberturas vegetales y su relación con actividades antrópicas (amenazas) presentes en el Parque Nacional Natural Tatamá y su área de influencia.. 309 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 41 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 76 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 69 records from BIRDRACE Pfeifenten. 54 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 11 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 39 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 146 records from Données de la naturaliste Laurence Beauchamp. 61 records from Knechtweide (Kohlfurth). 2525 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 30 records from Collections ichtyologiques et herpétologiques (BOUM). 85 records from MCP-Mamiferos - Coleção de Mamíferos. 18 records from Benthic macrofauna abundance of sediment core 12930-073. 288 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 1 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 13481 records from Données naturalistes de Bruno OGER. 15029 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 358 records from Données du Syndicat de la Vallée de l'Orge Aval (SIVOA). 89 records from Meniscus Midges (Dixidae) of Ireland. 14 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 40 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 493 records from Occurrence database of native plants and animals of south-central Chile. 13 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 83 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 11 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 6186 records from NE Scotland fish records 1800-2010. 92 records from Natura 2000 Parc naturel régional de Lorraine. 144282 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 1342 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 2 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 830 records from Zambian Bat Collections Worldwide. 1 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 14 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 116 records from Pollen profile ADR353. 143 records from BIRDRACE Punkbirder Helgoland. 6 records from Sächsische Schweiz (Pfaffenstein). 564 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 554 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 27 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 4 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 2 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 4335 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 37 records from Living Cirripedia. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 29 records from Nannofossil abundance of Hole 4-29. 2017 records from Helmintos parásitos de peces del sureste de México. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 67 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 28 records from Naturpark Kottenforst-Ville 15.6.09. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 38 records from Roter Berg Werdau (Leubnitz). 218 records from Land and freshwater molluscs of Northern Spain. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 2 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 10 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 466379 records from DNV GL Sleipner. 127 records from FFH-Gebiet Klosterwasser/Burkau. 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 24633 records from University of California Santa Barbara Invertebrate Zoology Collection. 256 records from Données naturalistes de Hubert GUIMIER. 1532 records from Données naturalistes de Hervé BOUYON. 1801 records from Données de la collection Rousset -1947-2013. 2 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 76 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 254 records from Thistle Heads and Ermerged Insects. 76 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 60367 records from Entomology Collection at the Natural History Museum of Utah. 3121 records from Données DREAL Centre-Val de Loire - Faune - 2018. 114 records from BIRDRACE LiLaLau. 71228 records from Fish specimens of Kagoshima University Museum. 39345 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 3803 records from UTEP Invertebrates (Arctos). 104 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 33 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 26 records from Schulteich Freie Waldorfschule Darmstadt. 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 9053 records from Highland bird data 2002 - 2003 - non-breeding records. 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 140 records from Foto trampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 22052 records from CNIN/Abejas de México/Apoidea. 3497 records from RNF - Données du Parc Naturel Régional du Vercors. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 54 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 2551 records from Insectes Hyménoptères Scollidés de France. 3515 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 577 records from Ensemble des données Odonates. 75 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 2017 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4303 records from Weddell Sea macrozoobenthos EASIZ I. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 1 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 916 records from IOW Natural History & Archaeological Society Marine Records. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 2194 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 5398 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 1407 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 2099 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 8 records from Seawater metagenome Targeted loci environmental. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 12 records from Art´n Vielfalt im Kinderwald. 47 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 81 records from Waldi-Weiher. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 13 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 23 records from Benthic macrofauna abundance of sediment core 13077-093. 175 records from Invasive Non-Native Species, Outer Hebrides. 18 records from Phase 2 Lowland Grassland Survey of Wales. 296 records from Gewann Krampf (Heilbronn). 1397 records from Naturalis Biodiversity Center (NL) - Crustacea. 3 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 44 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 24 records from Données de NICOLAS Vincent (SAPROX). 24 records from Benthic macrofauna abundance of sediment core 13201-002. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 29 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 4 records from Pollen profile from Muscotah Marsh B. 48 records from Catch related distribution of Appendicularia at station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 8). 30 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 1 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 3 records from The larva of Lestes alfonsoi Gonzalez & Novelo (Zygoptera: Lestidae). 1145 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 975149 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 413272 records from DATAVES. 2 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 3 records from seawater metagenome Metagenome. 23 records from Herpetofauna asociada a la cuenca del río Quito - Chocó, 2014. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 2436 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 27 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 3767 records from Heliconiine Butterfly Collection Records from University of Cambridge. 720 records from The Broward College Insect Collection. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 357 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 56 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 79 records from Birdrace-Bielefinken-Bielefeld. 9653 records from Ecosphère_2017_12_18. 4054 records from Fish specimens of Toyama Science Museum. 8685 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 121 records from Range table from ostracoda in ODP Hole 143-866B. 49 records from Müritz-Nationalpark. 16 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 1763 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 2560 records from Upper Silesian Museum, Bird Observations. 9 records from Range table from benthic foraminifers in ODP Hole 146-889A. 1124 records from Données naturalistes de Quentin ROME. 1 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 141 records from Bannwald Burghauser Forst. 127 records from SEWBReC Springtails and allies (South East Wales). 192 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 21160 records from SEWBReC Bees, Wasps and Ants (South East Wales). 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 15 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 10 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 7 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2125 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 77 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 3 records from Benthic foraminifera and algae abundance of Hole 81-552A. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 15037 records from University of Guam Insect Collection. 30 records from Artenvielfalt des "Grünen Klassenzimmers". 2 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 45 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1056 records from UWIZM Molluscs. 4007 records from MCP-Aves - Coleção de Aves. 12 records from Nannofossil abundance of Hole 36-329. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 103 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 776 records from Bird specimens of Saitama Museum of Natural History. 371 records from orthopteracollections-nhmj-ioj. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 2915 records from Collections of Bioclass, school #179, Moscow. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 13 records from Inventaire des Octocoralliaires des fonds sédimentaires de la région niçoise. 2 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 17 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 160 records from UWIZM Anoles. 4 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 89 records from Pollen analysis of sediment profile TR0 from Truennensee. 2374 records from Macrobenthos Chukchi Sea, 1986. 20 records from Condamine Alliance. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 8 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 366 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 15 records from Tardigrad collection of the National Museum of Nature and Science. 43 records from Faunal assemblage of sediment core TR149-31. 29 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 18 records from Naturtag. 17 records from données espèces - Expertise IPE 63. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 744 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 9 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 21837 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 6178 records from Plecoptera. 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 5 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 167 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 11 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 14 records from NZCS Brownsberg Nature Park Monitoring. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 62110 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 15 records from Suivi de la colonie de Pipistrelles de la Petite Ceinture à Paris. 21 records from Riedkanal Bötzingen. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 54 records from Aves marinas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 1029185 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 4 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 15 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 2 records from A Catalogue and Historical Study of the Odonata of Ecuador. 4617 records from Códigos de barras de la vida en peces y zooplancton de México. 2 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 4 records from Loricifera - SMF. 9 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 479121 records from KTP Ring Data. 1 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 11 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 16437 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 1109 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 4 records from Soil metagenome from healthy and unhealthy agricultural soil. 23 records from Morphologische Daten von Natrix. 2 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 14 records from Brown University Herbarium. 26 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 89 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 689 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 21 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 695 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 303 records from CNAC/Coleccion Nacional de Acaros. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 622 records from hauterivian_echinoids_of_the_paris_basin. 27 records from Nannofossil abundance of Hole 4-31. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 14 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 99 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 68 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 7 records from TransForest - vegetation, lichen and fungi data 2016. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 126 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 9 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2. 4 records from CEFS_16S_ITS. 17892 records from Biowide Species data. 11 records from Inventaire Natura 2000 Zones humides de Moliets, la Prade et Moïsan 2006/2008. 1194 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 13 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 8 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 203 records from Schanzenanlage Bergham. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 22 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 75 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 549 records from Données du Geckos vert des Hauts (Phesulma borbonica) du Parc national de La Réunion. 6 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 1 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 6 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 7 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 59 records from Nannofossil abundance of Hole 37-334. 20 records from Schulgelände SGD/Viersen. 1511 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 53 records from Leopard and Weddell seal program 1999/2002. 2543 records from Données naturalistes de Ségolène FAUSTEN. 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 4 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 8851 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 7079 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 39 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 13644 records from Collection of Coleoptera. 11 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 37 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 2 records from Unveiling the morphology of the Oriental rare monotypic ant genus Opamyrma YAMANE, BUI & EGUCHI, 2008 (Hymenoptera: Formicidae: Leptanillinae) and its evolutionary implications, with first descriptions of the male, larva, tentorium, and sting apparatus. 366 records from Ensemble des données Rhopalocères. 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 2 records from uncultured prokaryote Targeted loci environmental. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 19 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 84 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 4649 records from Colección Limnológica Universidad de Antioquia. 378 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 503 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 92 records from Wald am Schloss Wittgenstein Bad Laasphe. 140524 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 223 records from Shoreline fish distribution in Italian lakes assessed by electrofishing. 58 records from Isle of Wight non-native invasive species. 2 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 6488 records from Données naturalistes de LUPOLI Roland. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 68 records from Données du/de la naturaliste JOSSERAND oriane provenant de la base de donnée du SINP Île-de-France CETTIA. 90 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 2 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 335 records from Données naturalistes de François BRETON. 8 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 21 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 4 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 57 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 59 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 5 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 28 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 24430 records from EDP Foz Tua: Terrestrial Birds, Winter (point counts) - Ecological Monitoring Program [2011-2017]. 5 records from Die Bachspezies 2008/2009. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 4 records from Results of palynological analysis of Hole 302-M0004C. 12 records from Lepidoptera specimen database of Japan. 1 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 2499 records from Leicestershire and Rutland Reptile Records to 2011. 294817 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 45139 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 23 records from Smear slide analysis on sediment core GeoB4214-1. 23 records from Abundance of benthos infauna at station GIK23042-2. 5 records from Streuobstwiese. 327 records from Collection Vermes - ZMB. 130 records from BIRDRACE - The famous Grouse feat. The James. 442005 records from Western Australian Museum provider for OZCAM. 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 3 records from Parasitoides de Cochinilla. 418 records from Mamíferos voladores y no voladores del suroccidente colombiano. 43 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 760 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 2 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 372 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 6 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 4 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 6 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 21 records from Waldstück am Schullandheim Bad Bederkesa. 170 records from Coarse fraction analysis and texture of biogenous sands from Josephine Seamount surface samples (Table 2). 23 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 1461 records from M. Gollop Collection. 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from Données naturalistes d'Olivier DELZONS. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 26 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 1929 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 1268 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 153 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1. 36 records from (Tab. 6) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 41-370, Deep Basin West off Morocco. 23 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 4 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 4 records from Society Islands beach bum black flies (Diptera: Simuliidae). 5496 records from Abondances et caractéristiques biologiques des juvéniles de saumons échantillonnés lors des indices d'abondance du saumon dans la rivière Nivelle (France). 9 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 2722 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 53 records from Données naturalistes de BONCHE Jérôme. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 28 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 438 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 79758 records from natagora-earlybirds. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 9 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 6747 records from Hormigas del Museo de Entomología de la Universidad del Valle. 11 records from Reptiles Specimens of Akita Prefectural Museum. 3 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 88 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 204 records from UWIZM Snakes. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 36 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 16 records from Insect Collections of Okomu National Park- Nigeria. 43225 records from University of Minnesota Insect Collection. 270437 records from ARABEL - Arachnologia Belgica. 124519 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 218 records from Heinersdorfer Sumpfwiese. 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 10552 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 22176 records from Arctic Species Trend Index (ASTI) : Marine. 7 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 1 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 33409 records from Wolli Creek Preservation Society Bird Survey. 43 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 141 records from Biodiversity survey of Rugezi wetland, Year 2013. 60940 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 4 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 4 records from Crustáceos del municipio Santa Bárbara, Santander - Proyecto Santander BIO. 110 records from Etude écologique du Parc des Lilas (94). 3 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 11 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 7247 records from Colecção Entomológica IIA. 16687 records from MZFC/Coleccion de Aves. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 1057 records from DMNS Egg Collection (Arctos). 13159 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 3 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 5461 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 287870 records from Florida Keys Reef Visual Census 2014. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 2 records from A practical introduction to microbial molecular ecology through the use of iChips. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 3753 records from Données naturalistes de Charlotte PICARD. 5 records from Ostracoda abundance of Hole 44-390. 3 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 226 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 878 records from Données de la structure SNPN - Société Nationale de Protection de la nature provenant de la base de donnée du SINP Île-de-France CETTIA. 1121 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 10696 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 2872 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 19617 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 139 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 129 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 35 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 141 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 92 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 529 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 10 records from Ostracoda abundance of Hole 32-306. 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 49 records from Lebensraum Gesamtschule (Langerwehe). 13 records from Foraminifera abundance of Hole 64-481. 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 26 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 96156 records from Butterflies of Ireland. 17 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 2 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 684 records from Coléoptères Silphidés du département du Loiret. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 68269 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27116 records from Formidabel; Belgian Ants Database. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 3 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 43 records from New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957. 476 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 70 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 16 records from Hazel Dormouse in Ireland. 1 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 8 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 4 records from Nannofossil abundance of Hole 67-499B. 16 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 41676 records from Tagged Seal Location Data from SOGLOBEC. 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 417 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 333 records from Données naturalistes de Renaud PUISSAUVE. 310556 records from Dry Tortugas Reef Visual Census 2010. 237 records from Suivi ornithologique par IPA et IKA réalisés dans la Réserve nationale de l’Étang de Saint-Paul en 2012 et 2014. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 2 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 282 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 175 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 1709 records from The Gibson spider collection. 47 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 34 records from Naturgrundstück (Eutin). 7 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 8 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 95 records from Truppenübungsplatz Panzerkaserne Böblingen. 1 records from The Calliphoridae (Diptera) of Armenia. 651 records from Réseaux écologiques/Trame verte et bleue. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 14 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 229 records from données araneologiques de LEENKNEGT Virginie. 3 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 66164 records from Florida Keys Reef Visual Census 1996. 7950 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 46 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 52643 records from Données de l'Observatoire de la Faune de Bourgogne. 16 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 166 records from Neogene palynomorpha from site 93-603, part 2. 4117 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 228621 records from Wild bees of Belgium. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 4 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 3 records from Review of the genus Pseudolathra Casey, 1905 (Coleoptera: Staphylinidae: Paederinae) of Réunion Island. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 55 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 539 records from Phenological Center - Birds (Murmansk). 89 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 5 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 4142 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 185 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 277 records from Echinoderms from the Seaflower Biosphere Reserve. 10 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 558 records from If_Ecologie_Conseil_2017_12_18. 654 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 1 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 10 records from Analyses of the recent components of sediment core PS1011-1. 50726 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 9113 records from Royal British Columbia Museum Entomology Collection. 22 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 323 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 1123 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 280 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 28 records from MVZ Herp Observations (Arctos). 29 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 157 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 7 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 93 records from Journal of Hymenoptera Research. 7 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 994 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 143 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 8366 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 2981 records from Colección Entomológica CDMB. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 658 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 3 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 78 records from Données de la naturaliste Anna Even. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 17961 records from River Biologists' Database (EPA). 66 records from Selztal bei Friesenheim. 1457 records from UCM Mammal Collection (Arctos). 18 records from Microzooplankton abundance and biomass at station TT045_19-3. 94763 records from Tiroler Landesmuseum Ferdinandeum. 69 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 43 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 13868 records from Données faune Nature 18 - 2017. 2 records from Natural History Museum, Vienna - Herbarium W. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 8851 records from Odonata records from RSPB Reserves 1970-2009. 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 9 records from A new species of Proterhinus Sharp, 1878 (Coleoptera: Curculionoidea: Belidae) from Miti‘aro, Cook Islands, South Pacific. 854 records from Données supplémentaires Atlas des Mammifères marins. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 1962 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 7 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 18 records from Anfibios presentes en el Cerro Jánano. 26 records from Données espèces - Expertise IPE 79. 25 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1582293 records from NBIS Records to December 2016. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 132 records from Rohrmeistereiplateau und angrenzendes Gebiet. 859 records from Floral visits on plants, InsectScale 2008. 66 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 6 records from NZCS Invertebrates New Collection After 1987. 251 records from Données naturalistes d'Olivier LAURENT. 2147 records from Restauración y conservación de Isla Guadalupe. 16927 records from Lepidoptera (Specimens NRM). 13 records from Coleção de Coleoptera da Universidade de Brasília. 5044 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 993 records from ROC RSPB Farmland Species Survey Dataset. 205 records from Wild boar sightings held by Andy Riches. 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Brücke / B1. 6 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 182049 records from Florida Keys Reef Visual Census 1999. 23 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 94 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 318 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 27717 records from Collection of saproxylic and xylobiont Beetles. 202122 records from National Benthic Inventory. 2 records from Two new species of Helicopsyche Siebold 1856 (Insecta: Trichoptera: Helicopsychidae) from Pará State, northern Brazil. 195 records from EDP Foz-Tua: Nocturnal Birds - Complementary Studies [2010]. 16 records from Phenological Center - Fishes (Murmansk). 9 records from Steinbock (1937) Turbellaria XIV. The fishery grounds near Alexandria. Notes and Memories of the Fisheries Directorate of Egypt, No. 25. 111 records from BIRDRACE Die Wendehälse. 22070 records from Tachinid Recording Scheme - GB and Ireland records. 21 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 53 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 6 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 8332 records from Scotland Otter Survey Database. 4 records from Données naturalistes de Mikaël PAILLET. 13 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto120-128. 4607 records from Données de type contact en Guadeloupe. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1037 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 1 records from The Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) of Nepal. 672 records from The Sphecid Wasps of the genus Cerceris L, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from the Palearctic Region (part II). (Hymenoptera, Apoidea, Crabronidae). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 8 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 1304 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 38 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 2 records from Sächsische Schweiz (Wehlener Gebiet). 11 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 8985 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 42 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 3 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 113 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 528 records from Expedición Providencia I - INVEMAR. 2 records from Contribution to the tribe Pentoffiini (Cicadellidae: Evacanthinae) with descriptions of two new species and the male of Evanirvana aurea Hill, 1973. 7 records from Description of lithologic section units of IODP Hole 325-M0050A. 185 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6042 records from Arthur Chapman Observations. 307 records from Cuxhavener Küstenheiden. 188379 records from University of Michigan Museum of Zoology, Division of Birds. 285 records from (Table 2) Fossil record of foraminifera and ostracoda from Muldsberg clay pit, north Germany. 1434311 records from Hatikka Observation Database. 2347 records from UWYMV Bird Collection (Arctos). 18 records from Données naturalistes de Monsieur JOURDE Rémi. 249 records from Données naturalistes de AUNEAU Florent. 16 records from Foraminifera abundance of Hole 61-462. 6 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 118659 records from inatura - Erlebnis Naturschau Dornbirn. 5 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 14 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 1 records from Redescription of Chrysidea pumiloides Zimmermann, 1956, and description of three new species of Chrysidea from Madagascar (Hymenoptera: Chrysididae). 76 records from (Table 1) Counts and concentrations of pollen, spores and dinoflagellate cysts in sediment core MD01-2378. 30 records from Collection Graptolithina fossil SMF. 9 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 844 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 1132842 records from PlutoF platform observations. 2 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 40 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 10 records from Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense— 18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov.. 5 records from The endemic Southern African genus Epirinus Dejean, 1833 (Coleoptera: Scarabaeidae: Scarabaeinae) revisited: five new species and two new synonyms. 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 15 records from Benthic macrofauna abundance of sediment core 13078-015. 4 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 95 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 48 records from Zoo Frankfurt. 3515 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 203 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 128 records from BIRDRACE Oostfreesland Bird-Lopers. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 4 records from A new species of freshwater crab of the genus Phallangothelphusa Pretzmann, 1965, from the foothills of the Serranía Yariguíes of Colombia (Crustacea: Decapoda: Pseudothelphusidae). 114 records from Canada_BasinMegabenthos2002. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1081 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 10075 records from Nematoda of Costa Rica (INBio). 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 62 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 641 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 14 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 237 records from Capercaillie national surveys. 30 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 798 records from Regroupement de données rhopalocères et odonates 2015/2016. 9072 records from WTSWW Data: All Taxa (West Wales). 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 372 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 428 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 47 records from Données espèces - Expertise IPE 10. 63 records from Marine gastropod distribution from patagonian shallow waters. 54 records from "Ahrschleife bei Altenahr". 34 records from Salticidae (Arachnida: Araneae) of New Caledonia: Genus Corambis Simon, 1901. 9 records from A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae). 300658 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 1 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 19 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 35354 records from SIO Benthic Invertebrate Collection. 7830 records from DASSH Data Archive Centre volunteer survey data. 405470 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 71659 records from CAS Invertebrate Zoology (IZ). 41 records from Etude d'impact projet d’ouverture de carrière à Vaudoy-en-Brie. 1 records from water Raw sequence reads. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 6 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 8 records from See lilies of the genus Bathycrinus (Echinodermata, Crinoidea: Bathycrinidae) from the North-West Pacific hadal trenches. 6 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 44289 records from Insects, Outer Hebrides. 99 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 798 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 117 records from Suivi des leucorrines sur 3 ans sur le site du Marais du Plata (partenariat CPIE SA, D40 et FDC40). 34 records from An der Ohm, (Wettsaasen). 185 records from Inventaire des odonates d'intérêt communautaire Midouze 2005. 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 10 records from Nannofossil abundance of Hole 73-521A. 1322 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 515 records from Kenai National Wildlife Refuge, Alaska (KNWR) Bird observations (Arctos). 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 8848 records from EDP Baixo Sabor: Birds - Construction and Reservoir Filling Phases - Vilariça Stream (MC1) [2013-2014]. 8 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 148 records from Abundance of birds in the Lena Delta Region. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 32 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 117 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 3 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 1 records from Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae). 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 4 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 16745 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 6761 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 505 records from National Frog Survey of Ireland 2010/2011. 2 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 5243 records from Colección Ornitológica de la Universidad del Valle. 585 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Kivach. 183 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 111 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 10 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 1 records from Untangling convoluted taxonomy of Chambriella Rego, Chubb & Pavanelli, 1999 (Cestoda: Proteocephalidae), with erection of Riggenbachiella n. g. and the description of a new species from pimelodid catfishes in the Neotropical Region. 2763 records from Marine Turtles. 610 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 188 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 14 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 499 records from Chronicle of Nature - Phenology of Birds of Central Forest State Nature Biosphere Reserve. 47 records from Unter hellen Zinnen und finsteren Grotten. 490 records from Insectos de la expedición en el páramo de Ocetá, Boyacá - Proyecto Boyacá BIO. 119 records from BIRDRACE Immerwiederhopf. 3 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 96 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 2361 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 37 records from Caracterización de Reptiles de las lagunas del municipio del Medio Baudó. 5 records from Collection Malakologie - SMNG. 2693 records from Grand Voyeux - Suivis scientifiques. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 77 records from UWIZM Cnidarians. 439 records from Antarctic and Subantarctic Asteroid zoogeography. 24 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 28 records from Nannofossil abundance of Hole 67-499. 286 records from Coastal and Marine Species Database. 78 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 12774 records from Carabid Collection (Pinned Vouchers). 535 records from Convention Fédération française de golf - MNHN 2016-2019.. 146317 records from Tasmanian Museum and Art Gallery provider for OZCAM. 938 records from TTRS Mammals. 54 records from Weidegebiete in der Selzrenaturierung. 744 records from Ostracoda in sediment core PS51/159-10. 236 records from Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 22 records from Avifauna de los bosques húmedos y remanentes de Tierralta - Córdoba, 2011. 1365363 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2018.. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 579 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 3 records from A new species of Mada Gordon from the Andes (Coleoptera: Coccinellidae: Epilachnini). 1811 records from Point Count Data for TIDE's Private Land (Kern), Belize 2009-2013. 45 records from Brown bear monitoring data from Deosai National Park. 199 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 3 records from A new species of Paraproto (Crustacea: Amphipoda) from southern New SouthWales, Australia. 5894 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 9 records from UTEP Fish (Arctos). 9 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 111 records from Birdrace-Uhulogen-Lippe. 3319 records from Collection Aves (bird skins) SMF. 1 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 635 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 15 records from Feral Pigs - Sightings and Cull records - 2018-2019. 43 records from Taxonomic revision of the genus Probolomyrmex Mayr, 1901 (Hymenoptera: Formicidae: Proceratiinae) for the Neotropical Region. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 4054 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 4 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 7 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 370 records from Otter survey of Ireland 2004 & 2005. 2 records from Description of a new species of Liocheles Sundevall, 1833 (Hormuridae) from India. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 84 records from BIRDRACE Vogelscheuchen. 11 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 4 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 81 records from Birdrace-Die_Ornithomaten-Herford. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 14 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 917 records from Área Galeras - Monitoreo de Aves abril-octubre, 2018. 1 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 80648 records from NINA Vanndata fisk. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 3 records from Microbial diversity in shallow water hydrothermal sediments of Gueishan Island, Taiwan. 510 records from Inventaires des cygnes du département de l'Eure. 10 records from Landwehrbach. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 27 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 9632 records from CSIRO, fish surveys by the Soela, 1980s. 25 records from Herpetofauna de la expedición Piedemonte Llanero - Proyecto Boyacá BIO UPTC. 31 records from Artenvielfalt in der Kinderakademie im RFZ. 96 records from Peces de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 3 records from A new species and additional records of brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China and Taiwan. 4 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 3275 records from Trawl-survey data from the “expedition Hvar” in the Adriatic Sea (Mediterranean) collected in 1948-1949. 295 records from Données de VINCENT Alexis (SAPROX). 25 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 215 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 53062 records from British Antarctic Survey Argos satellite tracking data. 1100 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 2 records from Contribution to the taxonomy of the paper wasp genus Polistes (Polistella) (Hymenoptera: Vespidae: Polistinae) from Vietnam, with description of a new species. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 7 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 600 records from Growth and age across range extension region of Centrostephanus rodgersii in eastern Tasmania and morphometric comparison of urchins inhabiting kelp versus barrens habitats, Australia (2004-2005). 23 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 8230 records from University Of Pretoria: Lacewing Database Project (1911-2015). 20 records from Freiheitsring (Frechen). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 2782 records from USAC Mammals Collection. 588 records from Données du naturaliste Doux Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 35 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 29280 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 588 records from Données du naturaliste Christian Desmier. 6992 records from Stone-curlew Annual Surveys. 111 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 9 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 3160 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 97 records from Avifauna asociada a las fuentes abastecedoras de agua en La sierpe - Osbezcac (rio Saija, Timbiquí - Cauca). 836 records from Odoanta of Akwa Ibom State University, Nigeria. 239 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 78 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 1 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2232 records from Données naturalistes de Bernard Lalanne-Cassou. 8006 records from Données naturalistes de Franck NOEL. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1470 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 105465 records from Arizona State University Hasbrouck Insect Collection. 11 records from Description of lithologic section units of IODP Hole 325-M0055A. 63364 records from CCAMLR historic KRILL. 94 records from Quarrendorfer Landschaftsschutzgebiet. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 162 records from Registros de quirópteros de tres localidades del caribe colombiano. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 3576 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 9982 records from EDP Foz-Tua: Large Mammals (diurnal transects): Ecological Monitoring Program [2011-2017]. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 10 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 1 records from Range table from planktonic foraminifers in ODP Hole 170-1039B. 27 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 14 records from BMHS Crustacean Collection. 167 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB3603-2. 42 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 87546 records from MDFRC macroinvertebrate survey. 55 records from Données naturalistes de Pauline BALDUCCI. 17 records from Amtsrain Apolda-Zottelstedt. 1 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 136 records from Inventaire des reptiles 2014 pour les Atlas communaux de la Biodiversité du PNRLG. 135 records from DIBA-Parc del Montnegre i el Corredor. 4752 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 196 records from Données du/de la naturaliste LELARDOUX LOIC provenant de la base de donnée du SINP Île-de-France CETTIA. 457 records from MoJ BioBlitz August 2018. 5 records from Planktic foraminifera abundance of Hole 40-362A. 53 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 1126 records from JRS Wetands data Rwanda, 2019. 36 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 1 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 16256 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 7 records from Grundwasserlebensraum im Englischen Garten (München). 17 records from Description of lithologic section units of IODP Hole 325-M0043A. 1 records from Review of the genus Bythonia Oman 1936 with description of a new species and new record from Venezuela (Hemiptera, Cicadellidae, Iassinae). 213 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 1 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 1 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 8 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 2834 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 31 records from Caracterización Ecológica de los Macroinvertebrados de las Fuentes Hídricas presentes en el Cerro Jánano. 12846 records from MCP - Coleção de Abelhas. 527 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 19 records from Erhard Sopp. 306 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE293. 135 records from Recensement des chiroptères 2012/2014 - Atlas de la biodiversité de Bordeaux Métropole. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 1 records from Charinus rocamadre (Amblypygi, Charinidae): description of the female, ultrastructure of the male and female gonopods, and mitochondrial DNA sequences. 45 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 39 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 4 records from New species and new geographical records in Disteniidae (Coleoptera, Chrysomeloidea) with revised keys to species of Novantinoe and American species of Distenia (Distenia). 61 records from Shrews of Poland. 181 records from Données du/de la naturaliste Beutin Sabine provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Nannofossil abundance of Hole 2-11. 3362 records from Données naturalistes de Pascal Dupont. 5996 records from K-State Museum of Entomological and Prairie Arthropod Research. 18 records from suivi du site Natura 2000 Carrière Saint Nicolas. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 86 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 28062 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 2165 records from Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 181 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 3 records from Nannofossil abundance of Hole 6-48B. 29 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 1762 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 181184 records from Marine benthic dataset (version 1) commissioned by UKOOA. 25 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 973 records from Freshwater Fishes of Bulgaria. 38 records from Nannofossil abundance of Hole 4-25. 5229 records from European Moth Nights. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 803 records from Zootaxa. 73 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 6804 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 9983 records from NBMB Herps. 2 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 16 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 434 records from Aves de Caño Cristales, La Macarena, Meta. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 116 records from Umgebung der Gesamtschule Hamburg-Winterhude. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 11079 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 2617 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 4 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 525 records from BUND - Dassower See (Lübeck/Dassow). 12 records from (Table AT1) Planktonic foraminiferal stratigraphy of ODP Hole 182-1126B. 59479 records from Données naturalistes de Monsieur François FOURNIER. 63 records from Birds and plant species near Petushki town (Vladimir region). 380 records from NHMO DNA Bank Other groups collection. 833 records from Revues diverses et littérature grise.. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 114 records from (Table 4) Thecosomata in ODP Hole 134-831A. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 9 records from Jeu de données convention FEGVE-SPN (numéro 2). 1173 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 343 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 3320 records from BioGIS - Mammals - SPNI. 19 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 2369 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 90159 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 23806 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 917439 records from SEWBReC Birds (South East Wales). 75 records from Luderbusch. 39903 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 8 records from Teich im Wald zwischen Böblingen und Schönaich. 807 records from Área Galeras - Monitoreo de Aves, 2016. 2486 records from Collections data on ecology of bottom animal of the Southern ocean. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 110 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 7 records from DNA barcoding reveals a species group of the genus Campiglossa (Diptera, Tephritidae, Tephritinae) with recognition of a new species from East Asia and previously unknown females of Campiglossa coei (Hardy). 14 records from Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov.. 329 records from Collection Echinodermata SMF. 18333 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5017 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 2564 records from Fish Collection of Yokosuka City Museum. 238 records from Malawi-Cicindelidae-Biodiversity-Data. 3 records from Garra sindhi, a new species from the Jebel Samhan Nature Reserve in Oman (Teleostei: Cyprinidae). 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 11 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 32905 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 448 records from Données araignées de Corse par Canard A., Rollard C., Villepoux O.. 12 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6303 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 1 records from Description of lithologic section units of IODP Hole 325-M0052C. 2 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 72 records from Heavy minerals of sediment core PL94-64. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 5 records from Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic. 101787 records from Amphibiens et Reptiles de France (Enquête 2). 82 records from Wirbach-Taubental (Bad Blankenburg). 2851 records from Données naturalistes d'Alain BERLY. 26966 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 13 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 22 records from Données opportunistes récoltées par le Département des Landes jusqu'en 2015. 1698 records from Red-throated diver national surveys in Scotland - raw data. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 8400 records from Auburn University Museum of Natural History Mollusks. 7484 records from Yoann_BLANCHON_2017_12_18. 136 records from Inventaire et regroupement de données Natura 2000 Midou-Ludon 2012. 12863 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 77 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 3 records from MSB Mammal Observations (Arctos). 490 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 4968 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 56 records from Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 10 records from Données naturalistes de Sophie COHEN. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 24880 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 168 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 11 records from Review of the aquatic Hemiptera from Cephalonia, with a checklist for the Ionian Islands, Greece (Heteroptera: Gerromorpha, Nepomorpha, Leptopodomorpha). 124 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 194 records from Regroupement de données Oiseaux d'eau du Département des Landes durant les hivers 2016 et 2017. 29 records from Abundance of benthos infauna at station POS128/2_284. 748 records from Phenological Center - Birds (Laplandskiy). 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 528 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 57 records from Inventaire faune flore de l'étang d'Abbecourt à Orgeval. 108442 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 3 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 54 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 27986 records from Bird records for Argyll for the years 2002 and 2003. 2 records from SWECO. 3853 records from Données naturalistes de Loïc SALAUN. 4034 records from nsmk_fish_biodiversity_2019. 53 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 27 records from Ibaraki Nature Museum, Fish collection. 13871 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 24 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 34 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 460 records from Insectos recolectados en trampas Malaise en el departamento de Vichada - Proyecto Colombia Bio. 1939 records from East Ayrshire Species Database. 28483 records from Marine Biological Sample Database, JAMSTEC. 270 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 330 records from Otter (Lutra lutra), Outer Hebrides. 962 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 30 records from Ornitofauna de un Área Degradada por Actividad Minera en la Costa Caucana. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1519 records from Leif Richardson Vermont Bee Specimens. 11 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 3 records from A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps. 254 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 133 records from Données espèces - Expertise IQE 95. 3454 records from Collection Crustacea - ZMB. 874 records from The Living Murray Fish data. 66 records from Range table from ostracoda in ODP Hole 151-910D. 612 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 18 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 25974 records from Long-term Bird Census in Cigu 2004-2017. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 1287 records from CNIN/Tipos Coleoptera. 9 records from Fatkullina imitata n. sp., second species of a unique cheilostome bryozoan genus with reversed-polarity zooidal budding, and new family Fatkullinidae. 7 records from New and little known species of Eumolpinae (Coleoptera: Chrysomelidae) from Northern Vietnam. 47 records from Galls on Beech Trees in Hainich, 2008. 15 records from Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 2053 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 61628 records from CAS Entomology (ENT). 145160 records from Carnet B Lorraine. 5143 records from Naturalis Biodiversity Center (NL) - Pisces. 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 24 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 3 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 5 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 62089 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 299102 records from Seasearch Marine Surveys in England. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 41 records from Annales de la Société Linnéenne de Maine-et-Loire. 122 records from Comunidad íctica del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 1 records from New species of Ilanga (Gastropoda: Trochoidea: Solariellidae) from the Indo-West Pacific. 7 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 106 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 38 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 500 records from Chronicle of Nature - Phenology of Insects of Pechoro-Ilych State Nature Reserve. 53 records from Données malacologiques continentales de Julien Ryelandt (CORSE 2017). 9 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 1045 records from Collection Trichoptera - SMF. 10026 records from Insectes Hétéroptères Mirides de France. 1 records from Macrochelid mites (Mesostigmata: Macrochelidae) from São Paulo state, Brazil, with description of a new species of Macrocheles. 11 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 94 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 72 records from Range table from nannofossils in ODP Hole 164-994C. 23 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 11 records from Nannofossil abundance of Hole 1-3. 1552 records from Données du naturaliste ROCHAT Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 131 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 3 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and species from China (Coleoptera: Carabidae: Dryptini). 10 records from Nannofossil abundance of Hole 6-55. 2 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 3 records from Three new taxa of Noctuidae from China (Lepidoptera: Noctuidae). 100 records from Pollen analysis of sediment core GeoB6518-1. 80 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 1 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 40 records from The caddisfly genus Protoptila in Costa Rica (Trichoptera: Glossosomatidae). 4 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 92570 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 46 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 31 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 1066 records from Territorial Andes Occidentales - Densidad poblacional VOC subsistema cámaras trampa, 2018. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 90 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 28 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 4306 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 49 records from Faunal assemblage of sediment core TR149-32. 59 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1 records from Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae). 1913 records from Registros Primates Neotropicales Convocatoria APC. 2 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 82 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 8 records from Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) III. The trilineata species group, with descriptions of four new species. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 13 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 2 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 1 records from Systematics, Morphology and Biogeography Phylogeny of the Augochlora clade with the description of four new species (Hymenoptera, Apoidea). 14282 records from Mollusques dulcicoles de France - Jacques MOUTHON. 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 1011 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 610 records from BID-Malawi-Geometridae-Biodiversity-Data. 433 records from Inventaires odonates/Fadet des laîches 2014 par le CPIE Seignanx et Adour sur les sites N2000 FR7200716 et FR7200717. 11 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 31 records from Schulgelände Lise Meitner Realschule (Paderborn). 7 records from Contribution to the AIrotropical Ɨchneumoninae (Hymenoptera, Ɨchneumonidae) Irom Gabon and Sierra Leone, with descriptions oI Iive new species and two new subspecies. 322216 records from Carabidae records for Britain to 2014. 240 records from BARTH-Environnement_2017_12_18. 4 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 8 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 10 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 12 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 394 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 44 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 21 records from (Appendix A1) Calcareous nannofossil counts of ODP Site 207-1258. 4693 records from SANBI: DNA Banking(1987-2011). 27 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 14652 records from The national database for marine data (MADS). 1743 records from Naturalis Biodiversity Center (NL) - Mammalia. 16 records from Microzooplankton abundance and biomass at station TT043_11-1. 8 records from Foraminifera abundance of Hole 57-440A. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 4 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 4 records from Taxonomy of deep-water tetillid sponges (Porifera, Demospongiae, Spirophorina) from Brazil, with description of three new species and new characters. 1 records from A new Limnonectes (Anura: Dicroglossidae) from southern Laos. 3 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 573 records from Ghent university - Zoology Museum - Nematod Collection. 101 records from BIRDRACE Enger am Spektiv. 22 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 18 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 2877 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 6 records from Données naturalistes de CLERGET sylvie. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 2875 records from Regroupement de données "papillons menacés" collectées par les réseaux entre 1990 et 2012. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 5 records from Warnowufer Groß Klein. 4 records from Stadtrandlandschaft Apolda-Nord. 11 records from Annotated checklist of the Hemiptera Heteroptera of the Site of Community Importance and Special Area of Conservation “ Alpi Marittime ” (NW Italy). 26 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 45 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 15123 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 19 records from Nannofossil abundance of Hole 47-398. 13 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘ Bush Blitz’ surveys of national reserves. 626 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 14503 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 13 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 41 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 60 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1 records from Revision of the amphiamerican genus Mysidium Dana, 1852 (Crustacea: Mysida: Mysidae), with descriptions of two new species and the establishment of two new subgenera. 1 records from Two new species and new record of Amphinemura (Plecoptera: Nemouridae) from northern China. 13 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 1332 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1066 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 1 records from Taxonomy of Euschizomerus Chaudoir 1850 (Coleoptera: Carabidae: Panagaeinae) from India with a new species and new synonym. 8311 records from 成龍溼地鳥類生態紀錄. 2 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 208 records from MVZ Hildebrand Collection (Arctos). 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 21 records from Overview of the bee genus Trachusa Panzer, 1804 (Hymenoptera: Apoidea Megachilidae: Anthidiini) from China with description of three new species. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 48 records from New species and new records of terrestrial isopods (Crustacea, Isopoda, Oniscidea) of the families Philosciidae and Scleropactidae from Brazilian caves. 153 records from The ceratioid anglerfishes (Lophiiformes: Ceratioidei) of New Zealand. 475 records from Inventaire Faune Flore du Cirque de l'Essonne. 300 records from Records of Halieutichthys aculeatus complex (Ogcocephalidae, Lophiiformes). 1 records from Nannofossil abundance of Hole 58-442B. 3 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 50950 records from National Biodiversity Data Bank. Observation records, 1900-2014. 1477 records from Peces de la cuenca alta y media del río Bita, Vichada (Colombia). 326 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 7 records from A new species of Biffarius Manning & Felder, 1991 (Decapoda: Axiidea Callianassidae) from the intertidal coast of northeastern Brazil. 602 records from Occurrence database of bryophytes and native animals of southern Chile. 4 records from VFD-H: Heidenrod: Pferdeweide Mürth. 12394 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 50 records from Données 2015 de l'Observatoire de la Biodiversité des Forêts. 2660 records from California State University, Long Beach Mammals. 1 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 5 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 981 records from Monitoreo de la ocupación del Oso Andino Tremarctos ornatus en el Parque Nacional Natural Chingaza 2010. 5 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 1486 records from Données mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 2. 1357 records from Ostracoda in sediment core PS51/154-11. 71 records from Nottekanal, Klasse 7 - 10. 50 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 28 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 1 records from A revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 2 (Revision of the nervosa species group). 2863 records from Inventaire des Mollusques Sphaeriidae de France. 1584 records from données aranéologiques de CORNIC Jean-François. 8 records from Four new and three newly recorded species of Diduga Moore, [1887] (Lepidoptera Erebidae, Arctiinae) from China. 86 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 48 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 15 records from Données espèces - Expertise IPE 69. 11 records from Waldwiese. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 2829 records from Clare Biological Records Centre Dataset 2004-2007. 220 records from Expédition Karubenthos 2012 : données issues des publications. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 4 records from A new glass sponge genus (Hexactinellida: Euplectellidae) from abyssal depth of the Yap Trench, northwestern Pacific Ocean. 3838 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 13 records from Neotropical Acanthoderini (Coleoptera, Cerambycidae, Lamiinae): Synonymies and new status in some genera, new species, transferences and new distributional records. 2 records from The genera Agelosus Sharp, 1889 and Apecholinus Bernhauer, 1933 in Taiwan (Coleoptera: Staphylinidae: Staphylinini: Staphylinina). 174 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 15 records from Flora und Fauna im Brexbachtal. 3889 records from MICROBIS database. 190 records from Herpetofauna laguna El Tinije. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 123 records from Birdrace-Professorenteam-Münster. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 3239 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 3065 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 5 records from A new genus with three new species of free-living marine nematodes of the subfamily Desmodorinae (Nematoda: Desmodoridae), from the continental shelf off northeastern Brazil. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 235428 records from Swiss National Orthoptera Databank. 884 records from Données naturalistes de Laurent KREMMER. 2131 records from Dolichopodidae of Portugal - dataset 2009-2018. 3320 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 140 records from SNH Invertebrate Site Condition Monitoring 2015: Blind Moss SSSI. 5 records from Scorpaena regina, a new scorpionfish (Teleostei: Scorpaenidae) from the east coast of Queensland, Australia. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 4 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 45367 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 2 records from Morphology and phylogenetic analysis of two new species of deep-sea golden gorgonians (Cnidaria: Octocorallia: Chrysogorgiidae) from seamounts in the Western Pacific Ocean. 137 records from Palynological analysis of sediment core GeoB3910-2. 71 records from Steinbruch Mainz-Weisenau. 9 records from New bobtail squid (Sepiolidae: Sepiolinae) from the Ryukyu islands revealed by molecular and morphological analysis. 2749 records from Fauna y flora del municipio de Lipa, Arauca. 12705 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 92 records from A revision of the genus Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae). 13944 records from Observations du Grand dauphin du Golfe normand-breton. 229 records from Caracterización hidrogeológica para el diagnóstico ambiental de alternativas del proyecto hidroeléctrico San Bartolomé (ISAGEN y HMV).. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 1 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 9 records from Distribution of meiobenthos in sediment core M19_202-2 of the northeastern Atlantic (Table 1). 7 records from Nationalpark Harz Schul-AG Braunlage. 12844 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 27 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (2000m section). 594 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 4 records from NEW-1. 137 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 523 records from Anfibios de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 1 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 16 records from Description of Paracymbiomma gen. nov., a new genus of prodidomid spiders from the Neotropical region (Araneae: Prodidomidae) including a new troglobite species. 4 records from Nannofossil abundance of Hole 39-353. 3635 records from Fish: Records for Kent.. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 17 records from Biodiversity Surveys, South-east Arnhem Land. 93 records from Données du/de la naturaliste Fourrier Thibault provenant de la base de donnée du SINP Île-de-France CETTIA. 691 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 282 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 1 records from Marine sediment Raw sequence reads. 3 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 120 records from Tejidos asociados al estado de conservación y riesgo de extinción del ensamblaje de anfibios de tres páramos colombianos. 33 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 7 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida), II. 21 records from Benthic macrofauna abundance of sediment core 13200-045. 1054 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 509 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 37 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 3 records from (Table 3) Occurrence of benthic foraminifers in ODP Hole 116-718C. 60 records from Wichita State University Collection. 176 records from Bosque Mesófilo de Montaña de México. 193 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 266 records from Chronicle of Nature - Phenology of Insects of Volzhsko-Kamsky National Nature Biosphere Rezerve. 52 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 41 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 794 records from Macroarthropods, Narsarsuaq 2014, Greenland. 66620 records from Benthos monitoring in the intertidal mudflats of Pertuis-Charentais (Bay of Biscay) from 2004 on. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 409 records from Records of fish species in coastal lagoons from Municipality of Arta, for the period 1999-2011. 59 records from Landschaftspark St.Leonhard-Deisendorf. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 272720 records from Parc_National_de_Port_Cros_2017_12_18. 2275 records from Vermont Buprestidae Survey. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 2000 records from Diversidad y distribución de los copépodos (Cyclopoida) de las zonas áridas del Centro-Norte de México. 12 records from Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 40 records from Trimma tevegae and T. caudomaculatum revisited and redescribed (Acanthopterygii, Gobiidae), with descriptions of three new similar species from the western Pacific. 3 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 425 records from Collection ornithologique A. Maës. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 36 records from Mammal specimens of Komatsu City Museum. 3 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 6 records from Three new Cryptochetum Rondani, 1875 (Diptera: Cryptochetidae) from Yunnan Province, China and an identification key to Chinese species. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 10 records from Review of the leafhopper genus Anufrievia Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 883 records from Report on the Danish Oceanographical expeditions 1908-1910 to the Mediterranean and adjacent seas - Pelagic Polychaetes. 20144 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 17 records from Örtzemündung (Stedden). 909 records from Dinámica poblacional de la tortuga de carey (Eretmochelys imbricata) en su área de forraje. Río Lagartos, Yucatán. 7 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 46509 records from National Stag Beetle Surveys (Great Stag Hunts). 102 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 1190 records from Tracking data from a free-roaming female cheetah released into the Pilanesberg National Park, South Africa. 2931018 records from Eremaea. 109 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 145 (N.S) n° 38 (1), 2010 - Données faune. 86237 records from Marine Offshore Seabed Survey data held by JNCC. 74437 records from KUBI Ornithology Collection. 3566 records from FrogWatch SA. 33 records from Données naturalistes de Françoise SERRE-COLLET. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 316 records from Données naturalistes de Monsieur LEFEBVRE François. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 1230 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 712 records from Natural History Museum Rotterdam (NL) - Chordata collection. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 14 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 35 records from Species of Gnathophausiidae (Crustacea, Lophogastrida) collected off the west coast of Baja California, Mexico, during the TALUD cruises. 11 records from ALP-PAGES_2017_12_18. 2 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 6556 records from Colección Herpetológica (Anfibios) del Museo de Historia Natural de la Universidad Industrial de Santander. 1045 records from Données odonates de l'inventaire Odonates-Rhopalocères du Parc Naturel Régional des Landes de Gascogne entre 1999 et 2002. 242 records from Malawi-Histeridae-Biodiversity-Data. 184 records from Biologische Station im Kreis Wesel. 69 records from Schiller Gymnasium Hof 10b. 1992 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 119 records from Données du/de la naturaliste Mallard stephane provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from Planktic foraminifera abundance of Hole 7-64. 1 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 1 records from Museu Paraense Emílio Goeldi - Acanthocephala Collection. 1390 records from The Apterygota collection (EA) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 10 records from Bachabschnitt der Nette (Osnabrück). 2 records from Pollen profile from Seminary School Basin. 16 records from Microzooplankton abundance and biomass at station TT043_4-1. 91855 records from Données photographiques validées de la galerie du forum "Le Monde des Insectes". 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 2 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 322193 records from Florida Keys Reef Visual Census 2010. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 13737 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 37 records from Pollen data of trap CB4. 10 records from Valentin Moser Bats. 153 records from annex1. 252 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils at DSDP Hole 93-603B. 2 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 58 records from Draubiotop Lavamünd. 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 128 records from Extracellular DNA marine sediment Targeted Locus (Loci). 36 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 549 records from Netzfluegler_Raw1. 64 records from "Schwarzwassertal" bei Pobershau. 1 records from marine metagenome Targeted Locus (Loci). 24468 records from Plan de vertebrados de la Patagonia. 3 records from A revision of the genus Petta Malmgren, 1866 (Annelida: Pectinariidae), with two new species from deep waters of southeastern Australia, and comments on phylogeny of the family. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 92 records from Birdrace_TerraCamper-Münster. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 50 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 2 records from New species, genera, families, and range extensions of freshwater bryozoans in Brazil: the tip of the iceberg?. 33 records from AlgaTerra. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 134709 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 1 records from Endophallus structure: a promising tool for cryptic species identification in Timarcha Samouelle, 1819 (Coleoptera: Chrysomelidae: Chrysomelinae). 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 87 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 553 records from Danielsberg (Mölltal, Kärnten). 90 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 13000 records from LPO_PACA_2017_12_18. 1 records from Nannofossil abundance of Hole 39-353A. 3 records from On the taxonomy of the genus Pseudacronicta Kononenko, 2001 (Lepidoptera Noctuidae, Acronictinae): the identity of Acronicta omihsiensis Draeseke, 1928. 102 records from Données de la naturaliste Clélie Granger. 493 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 2 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 69 records from Inventario de Mamíferos Mámbita. 361 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 42033 records from Canadian Museum of Nature Mammal Collection. 2 records from A new morphologically cryptic species of Phyllomedusa (Anura: Phyllomedusidae) from Amazonian forests of northern Peru revealed by DNA sequences. 60 records from Caracterización de la fauna reptiliana asociada a la cuenca del río Atrato, para el estudio de su navegabilidad, Quibdó - Chocó, 2012. 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 6 records from Pollen and spore abundance of Hole 42-381. 262310 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 12 records from Naturpark Sternberger Seenland. 13 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 5 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 144459 records from Biodiversitätsdatenbank des Landes Salzburg. 10909 records from NCSM Mammals Collection. 27 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 3 records from Nannofossil abundance of Hole 52-418. 23 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 7 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 4312 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 11 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 931 records from DMNS Parasite Collection (Arctos). 235 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea in winter 1995. 3294 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 44 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 1434 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 74 records from Nannofossil abundance of Hole 64-476. 33 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 2677 records from Données naturalistes de Matthias COLIN. 91477 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 129433 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 1392 records from Cowan Tetrapod Collection - Herpetology. 1 records from The invertebrate host of salmonid fish parasites Ceratonova shasta and Parvicapsula minibicornis (Cnidaria: Myxozoa), is a novel fabriciid annelid, Manayunkia occidentalis sp. nov. (Sabellida: Fabriciidae). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 289 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 12448 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 5 records from Phytoplankton abundance at station CD46_0705C#4. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 4195 records from CASES2003_2004. 11 records from Hemmerder Schelk (Unna). 36544 records from Fife Nature Records Centre combined dataset. 93 records from First records of 31 species of butterflies and moths (Lepidoptera) in Cameroon, with remarks on their elevational ranges. 1 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 2 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 1 records from First record of Gauguin's blunt-nose lizardfish, Trachinocephalus gauguini Polanco, Acero & Betancur 2016 (Teleostei: Synodontidae) outside the Marquesas Archipelago. 9 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 3 records from Description of a new species of Music frogs (Anura, Ranidae, Nidirana) from Mt Dayao, southern China. 7 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 1 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 10 records from jamaica_invasive_alien_species. 35 records from Naturschutzgebiet Lochbusch-Königswiesen. 821 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 15 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 2 records from Bolletino del Museo Civico di Storia Naturale di Verona, Botanica Zoologica [2000-]. 9 records from Two new deep-water species of the genus Thorogobius (Teleostei: Gobiidae) from the upper continental slope of the Eastern Central Atlantic. 18 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 277 records from Programme de valorisation des zones humides chassées - volet Oiseaux. 53 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 6683 records from Odonata de Veracruz. 270 records from BIRDRACE Niederlausitz-Team. 2 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 1 records from A revision of the genus Boroecia Poulsen 1973 (Ostracoda, Halocypridae) with the descriptions of three new species. 49 records from Schulgarten Huttenheim (Philippsburg/Baden). 65 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 5 records from Planktic foraminifera abundance of Hole 18-173. 783 records from Moluscos Marinhos de Augusto Nobre. 159 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 1376 records from Projet avidune - campagne 2015. 6 records from Poissons et Crustacés d'eau douce de la Martinique. 6639 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 6217 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 364 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 7783 records from LACM Invertebrate Paleontology. 15 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 3 records from Medleria gen. nov. adds to the biodiversity of Flatidae (Hemiptera: Fulgoromorpha) in the island of Socotra. 375 records from CG04_2017_12_18. 1593 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014]. 723 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 589 records from Données du/de la naturaliste PIQUET Alison provenant de la base de donnée du SINP Île-de-France CETTIA. 377 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 4 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 248 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 3 records from Collection Ephemeroptera - SMF. 527 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 22 records from Microzooplankton abundance and biomass at station TT045_15-2. 10686 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 5 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 1015 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 286 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 228 records from FBIP: Identification of polychaetes used as bait. 96300 records from Denver Museum of Nature & Science - Entomology. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 7 records from The millipede family Paradoxosomatidae in the Philippines, with a description of Eustrongylosoma penevi sp.n., and notes on Anoplodesmus anthracinus Pocock, 1895, recorded in Malaysia and Sri Lanka for the first time (Diplopoda, Polydesmida). 371 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 312 records from BIRDRACE Gätkes Erben. 2 records from A new species of Cryptoperla Needham, 1909 (Plecoptera: Peltoperlidae) from Guangxi of China, based on male, female, and larval stage. 36 records from (Tab. 8) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 79-547B, Mazagan Basin west of Morocco. 67 records from Revision of the Eurybrachidae XIV. The Australian genera Olonia Stål, 1862 and Stalobrachys gen. nov. (Hemiptera: Fulgoromorpha). 46 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3708 records from Benthos counted on dredged samples during Valdivia cruise VA53. 6 records from Ontogeny as an important part of integrative taxonomy in tergipedid aeolidaceans (Gastropoda: Nudibranchia) with a description of a new genus and species from the Barents Sea. 13 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 124 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 75 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 216 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 197 records from EDP Foz Tua Otter (Lutra lutra) [transects] - Ecological Monitoring Program (2010-11). 761 records from Carabidae of the European North-East of Russia. 5066 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 103 records from BIRDRACE federleser. 182 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 4011 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 310 records from The Fishery Grounds near Alexandria.VII.Decapoda.By Heinrich Balss.(1936).Notes and memoirs No. 15. 4 records from Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species. 259 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 8 records from Otiorhynchus (Choilisanu s) theophrastus sp. nov. from Lesbos Island, Greece (Coleoptera, Curculionidae, Entiminae). 1 records from Dolichocephala Macquart of Thailand (Diptera: Empididae: Clinocerinae). 1040 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 1 records from A new genus of Oxypodina from Kyrgyzstan (Coleoptera, Staphylinidae, Aleocharinae, Oxypodini). 37 records from Palynological analysis of sediment core GeoB9508-5. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 3 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 65 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 25 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 504 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 6 records from Abundance of benthos infauna at station GIK23065-1. 21385 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 5462 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 2712064 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 1073 records from Relevé de collections de lépidoptères rhopalocères et de coléoptères saproxyliques.. 16 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 1 records from Sediment metagenome. 3 records from New species of Prolachesilla Mockford & Sullivan (Psocodea: ‘ Psocoptera’: Lachesillidae: Graphocaeciliini) from Bolivia and Mexico. 148 records from Mean density of total metazoan meiofauna and major taxa or groups in the top 10 cm of surface sediment on 25 different dates at DYFAMED station. 166410 records from BioFokus. 13708 records from Anymals+plants - Citizen Science Data. 205 records from Chronicle of Nature - Phenology of Insects of FSBI Zeya State Nature Reserve. 17894 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 1 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 4 records from Two new species of Nealiolus Mason (Hymenoptera, Braconidae, Brachistinae) reared from pest weevils (Coleoptera, Curculionidae). 3387 records from Données avifaune de Guadeloupe. 2 records from Description of a new subspecies of Prosopocoilus antilopus (Swederus, 1787) (Coleoptera: Lucanidae) from Annobón Island, Gulf of Guinea. 991 records from Données du/de la naturaliste CARON Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from First record of the genus Phanoperla Banks, 1938 (Plecoptera: Perlidae) from mainland China, with description of a new species. 21 records from Fifteen new species and a new country record of Labomimus Sharp from China, with a checklist of world species (Coleoptera: Staphylinidae: Pselaphinae). 9 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 3746 records from UMNH Reptiles and Amphibians Collection (Arctos). 793 records from CNAN/Scorpiones. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 1 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 165 records from Mortensen Th. And Steuer Ad. 1937. The fishery grounds near Alexandria. XIII Echinoderma. Notes and Memoirs No 21. Hydrobiology and Fisheries Directorate, Egypt. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae
Keywords: GBIF; biodiversity; species occurrences